УЗИЛИШГА ЭГА БЎЛГАН КОЭФФИЦИЕНТЛИ ИНТЕГРО–ДИФФЕРЕНЦИАЛ ТЕНГЛАМА УЧУН БИР ЧЕГАРАВИЙ МАСАЛА (Scientific journal of the Fergana State University, 2023)
In the article a boundary value-problem has been investigated for an integro- differential equation with discontinuous coefficients